SORPTION BEHAVIOUR OF 3-(3,4-DICHLOROPHENYL)-1, 1-DIMETHYL UREA ON SOIL - Okieimen, F E; Odagwe0, L E; Ikuenobe, C E (Biological Sciences - PJSIR, 2001)
The sorption capacity of three· soil samples containing organic matter between 0.52 and 1.66% and clay fraction between 1.30 and 4.60% for 3-(3,4-dichlorophenyl)-l,l-dimethyl urea (diuron) in aqueous solution was examined at 29°C. It was found that between 40 and 60% of the herbicide was adsorbed by the soils and that the sorption capacity depended on the total colloidal fraction of the soils. The soil/water adsorption coefficient , Kd, of the herbicide was used to assess the relative phytotoxicity of the herbicide in the given soils.